The relationship between age and sex with floor post traumatic stress disorder on flood victim in Sawahan village Rengel Tuban - mohammad ubaidillah faqih; Tiara Putri Ryandini (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2020)
Post traumatic stress disorder has become an important problem should be solved instead of another mental disorder sith a sindrom undergone by someone who get traumatic experience and they cannot forget what they have experienced. Many people get stress after flood disaster in their village the porposeof this reseach is to know the relation beterween age and sex with post traumatic stress disorder on flood victim in rengel tuban. The reseach design is corelational analitic with cross sectional time method. This reseath use sg intlusion and so respondent for reseath sample. The independent variable is age and sex, meanwhile dependent variable is post traumatic stress disorder. The tehnique sample used simple random sampling. The data insttrumen isn’t guesti name with spearman and koefisien kontingensi (α= 0,05).Basedon statistic result shous that variable dealts post traumatic stress disorder with Pvalue =(0,001) and there is signifioant relationship between sex variabel with post traumatic stress disorder wits P value = (0,565).From the absfraet abone we can conlude that to stoppost traumatic stress disorder we have to give support by listening all their burden then give sosial solution and supportto stay and closerto Allah SWT.